ZnO/TiO2/Ag2Se nanostructures as photoelectrocatalysts for the degradation of oxytetracycline in water - Changanaqui, Katherina (2020)
Optimized thin films composed of ZnO nanorods, grown after preliminary electrodeposition and successively coated with 3 layers of TiO2 and decorated with Ag2Se nanoparticles, were prepared onto glass FTO wafers to treat oxytetracycline solutions by photoelectrocatalysis (PEC). The coatings were thoroughly characterized by XRD, Raman and UV/Vis diffuse reflectance spectroscopy, confocal microscopy, FE-SEM, HRTEM, EDX and XPS. The synthesized films had a mean thickness of 1.19 mu m, length >500 nm and a bandgap of 1.85 eV, being visible-light photoactive. Good stability and reproducibility was obtained when treating 5 mg dm(-3) oxytetracycline solutions in 0.050 M Na2SO4 at pH 5.8, attaining 96.5% antibiotic decay after 360 min at an anodic potential of +1.0 V vs Ag vertical bar AgCl under irradiation with a 36-W blue LED lamp. Comparative photocatalysis and electrochemical oxidation treatments revealed an interference between the active sites where the oxidant species were generated, causing an efficiency loss in PEC. The antibiotic was also removed from urban wastewater, thanks to the additional attack of electrogenerated active chlorine, although at a slower rate due to parallel oxidation of the natural organic matter. A degradation route for oxytetracycline is proposed based on the five primary products detected by LC-QToF-MS. (C) 2019 Elsevier Ltd. All rights reserved.